Evaluation Of The Anti-anemic Activity Of Date Syrup In Wistar Rats - Touhami, Laiche Ammar; Ghemam Hamed, Amina; Badi, Salima (جامعة الوادي - University of Eloued, 2020)
The main objective of this study is to determine the effect of food intake of date syrup on the treatment of anemia. First, we used 3 samples of dates from different regions for the preparation of the syrup. We have studied certain criteria (physical, chemical, biochemical, microbiological); where the results showed that the prepared date syrup has a good hygienic quality, and of remarkable nutritional quality due to its ideal content with many properties, such as carbohydrate and protein content. To evaluate the anti-anemic properties of date syrup in rats, anemia is induced by a food having an iron deficiency. Date syrup, prepared from Djamaa dates, was administered by gavage of anemic rats at doses of 1000 mg / kg / day and 2000 mg / kg / day resulting in an increase in hemoglobin, red blood cell count, hematocrit and serum iron. Thanks to the results obtained, date syrup can be classified among the foods that help fight iron deficiency anemia.
Keywords: Date syrup; Iron deficiency anemia; Hemoglobin; Red blood cells and hematocrit.